Effects of repeated-sprint training in hypoxia induced by voluntary hypoventilation on performance during ice hockey off-season - Brocherie, F.; Cantamessi, G.; Millet, G. P.; Woorons, X. (International Journal of Sports Science & Coaching, 2023)
This study aimed to assess the effects of an off-season period of repeated-sprint training in hypoxia induced by voluntary hypoventilation at low lung volume (RSH-VHL) on off-ice repeated-sprint ability (RSA) in ice hockey players. Thirty-five high-level youth ice hockey players completed 10 sessions of running repeated sprints over a 5-week period, either with RSH-VHL (n = 16) or with unrestricted breathing (RSN, n = 19). Before (Pre) and after (Post) the training period, subjects performed two 40-m single sprints (to obtain the reference velocity (Vref)) followed by a running RSA test (12 × 40 m all-out sprints with departure every 30 s). From Pre to Post, there was no change in Vref or in the maximal velocity reached in the RSA test in both groups. In RSH-VHL, the mean velocity of the RSA test was higher (88.9 ± 5.4 vs. 92.9 ± 3.2% of Vref; p < 0.01) and the percentage decrement score lower (11.1 ± 5.2 vs. 7.1 ± 3.3; p < 0.01) at Post than at Pre whereas no significant change occurred in the RSN group (89.6 ± 3.3 vs. 91.3 ± 1.9% of Vref, p = 0.11; 10.4 ± 3.2 vs. 8.7 ± 2.3%; p = 0.13). In conclusion, five weeks of off-ice RSH-VHL intervention led to a significant 4% improvement in off-ice RSA performance. Based on previous findings showing larger effects after shorter intervention time, the dose-response dependent effect of this innovative approach remains to be investigated.